New Insight of Scaffold Based on Hydroxyapatite (HAp)/Bacteria's Nanocellulose (BN) for Dental Tissue Engineering - Anitasari, Silvia; Budi, Hendrik Setia; Shen, Yung-Kang; Arina, Yuliana Mahdiyah Da'at (European Journal of Dentistry, 2023)
Objective Bacterial nanocellulose (BN), derived from Acetobacter xylinum ATCC 237672, is a polymer that offers several desirable characteristics for scaffolds applications. To further enhance the characteristic of the BN scaffold, hydroxyapatite (HAp) from Anadara granosa and Achatina fulica can be incorporated. Therefore, the aim of the study was to characterize the physical properties of a three-dimensional (3D) scaffold made of HAp and BN.Materials and Methods The scaffold was developed using the cellulose immersion technique, where BN was soaked in HAp suspension for different duration (5, 10, 15, 20, and 25 hours). The physical properties that were evaluated included porosity, pore density, swelling ratio, and water retention.Results The HAp/BN 3D scaffold, which is considered a hydrogel material, exhibited favorable physical properties that can support cell survival. The total porosity of the scaffolds was 100%. There was no significant difference porosity among the groups (p > 0.05). The swelling ratio increased on day 1 and then sharply decreased on day 2. There was a significant difference between the groups on both day 1 and day 2 (p < 0.05). The scaffolds immersed in the HAp for more than 15 hours exhibited higher water retention compared to the other groups, and there was a significant difference between the groups on day 2 and day 4 (p < 0.05). The scaffold immersed for more than 15 hours exhibited a higher pore density compared to those immersed for less than 15 hours, and there was no a significant difference between the groups (p > 0.05).Conclusion Our findings suggest that the HAp/BN 3D scaffold, especially when immersed in HAp for 15 hours, possesses promising physical properties that make it suitable for various applications in dental tissue engineering.
Keywords: scaffold; dental tissue engineering; human well-being; physical properties